Strategi pengembangan pariwisata di kabupaten muaro jambi dengan pendekatan analisis SWOT - Dahmiri, Dahmiri (Jurnal Paradigma Ekonomika, 2022)
The purpose of this study is to obtain information and analyze various problems faced and find strategies in tourism development in Muaro Jambi Regency. Primary data sources were obtained from selected informants from various groups, such as the government, private sector, community, business actors, community groups and universities. Secondary data obtained from related agencies and literature. Data collection tools are in the form of interview guides and through direct observation or observation. Data processing uses qualitative methods with tools to analyze internal factors and external factors with a SWOT Matrix analysis approach. The results of the study concluded that development strategies that can be carried out in Muaro Jambi Regency are increasing the quality and quantity of tourism infrastructure to support tourism development, repairing various facilities at tourist destinations that are in poor condition and adding supporting facilities that are still lacking, increasing the role of government and society in overcoming forest fires in the Jambi Province area which often occur which causes a decrease in tourist interest in visiting and increasing public awareness to carry out maintenance of tourist objects that are owned, especially for people who live around tourist areas.